1987
DOI: 10.1007/bf01869333
|View full text |Cite
|
Sign up to set email alerts
|

Volume-sensitive taurine transport in fish erythrocytes

Abstract: Taurine plays an important role in cell volume regulation in both vertebrates and invertebrates. Erythrocytes from two euryhaline fish species, the eel (Anguilla japonica) and the starry flounder (Platichthys stellatus) were found to contain high intracellular concentrations of this amino acid (approximately equal to 30 mmol per liter of cell water). Kinetic studies established that the cells possessed a saturable high-affinity Na+-dependent beta-amino-acid transport system which also required Cl- for activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
2

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 49 publications
6
43
2
Order By: Relevance
“…This contribution has been described in invertebrates and also in mammalian tissues such as cardiac cells (Thurston, Hauhart & Naccarato, 1981), Ehrlich cells (Hoffmann & Lambert, 1983;Lambert, 1984;Lambert & Hoffmannn, 1993) (Fugelli & Thoroed, 1986;Kirk, Ellory & Young, 1992), the skate (Goldstein & Brill, 1990, the eel (Fincham, Wolowyk & Young, 1987) and the trout (Garcia-Romeu, Cossins & Motais, 1991), and also in the cyclostomes, hagfish and lamprey (Brill, Musch & Goldstein, 1992).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This contribution has been described in invertebrates and also in mammalian tissues such as cardiac cells (Thurston, Hauhart & Naccarato, 1981), Ehrlich cells (Hoffmann & Lambert, 1983;Lambert, 1984;Lambert & Hoffmannn, 1993) (Fugelli & Thoroed, 1986;Kirk, Ellory & Young, 1992), the skate (Goldstein & Brill, 1990, the eel (Fincham, Wolowyk & Young, 1987) and the trout (Garcia-Romeu, Cossins & Motais, 1991), and also in the cyclostomes, hagfish and lamprey (Brill, Musch & Goldstein, 1992).…”
Section: Introductionmentioning
confidence: 84%
“…It is usually observed that RVD is associated with stimulation of the Na+-independent efflux of taurine, while the Na+-dependent influx is actually diminished (Hoffmann & Lambert, 1983;Fugelli & Thoroed, 1986;Fincham et al 1987). Fish erythrocytes differ from other cells in that hyposmolarity activates not only the output but also the uptake of taurine via a sodium-independent mechanism (Fugelli & Thoroed, 1986;Fincham et al 1987). Trout hepatocytes may be unique in that the taurine efflux accelerated by cell swelling relates to the presence of both sodium and chloride in the medium, as shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a net loss of taurine, a non-protein amino acid, occurs during a RVD in fish red blood cells (e.g. see Fincham, Wolowyk & Young, 1987;Goldstein & Brill, 1990). Indeed, taurine and other amino acids, notably glycine and alanine, have been shown to contribute to a RVD in some mammalian cells, such as Ehrlich ascites tumour cells and rat heart (Thurston, Hauhart & Naccarato, 1981;Hoffmann & Lambert, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Fish erythrocytes respond to hypotonic swelling by inducing a loss of K Ï© and Cl ÏȘ and also a transport of taurine and polyols (2)(3)(4)(5)(6)(7)(8) similarly affected by various anion transport blockers (5,(7)(8)(9). Recent observations (10) show that: (i) expression of the trout anion exchanger AE1 (tAE1) in Xenopus oocyte elicits, in addition to anion exchange activity, both anion conductance and appearance of a passive taurine transport; (ii) a very tight correlation exists between expression of anion conductance and taurine transport; (iii) compounds that inhibit anion conductance also inhibit taurine transport; (iv) expression of the anion exchanger (mAE1) of mouse erythrocyte, a cell that does not release organic osmolytes in response to swelling, elicits anion exchange activity but neither conductance nor taurine transport.…”
mentioning
confidence: 99%